Variabel Makroekonomi Sebagai Determinan Saham Properti - Adrianna Syariefur Rakhmat (JSMA, 2020)
High population growth from year to year is one cause of the development of the property sector. These can be considered by the public to invest in stock of the property and real estate subsector. In investing decisions, investors must look at macroeconomic conditions that can affect stock price movements. The puspose of this studying to analyze the effect of macroeconomic factors, namely inflation, interest rates, and the exchange rate of rupiah on the stock price of the property and real estate. This research is a quantitative study using panel data regression analysis method and using software Eviews 10. The data used are monthly data obtained from monthly report of the Indonesia Stock Exchange, Bank Indonesia, and the Central Statistics Agency with the technique of recording or documentation. The sampling technique is done by purposive sampling and obtaining 420 data during 2014-2019 period in 7 property and real estate subsector companies listed on the Indonesia Stock Exchange. The result of this study show partial result, each inflation variable and the rupiah exchange rate has a negative and significant effect on the share price of the property and real estate subsector. While the interest rate variable has a negative but not significant effect on the share price of the property and real estate subsector listed on the Indonesia Stock Exchange during the study period. Keyword: Inflation, Interest Rate, Exchange Rates, Stock Price.